MODERN POSSIBILITIES OF APPLICATION OF PREPARATION NAVELBINE® IN THE TREATMENT OF METASTATIC BREAST CANCER - L. V. Bolotina (Исследования и практика в медицине)
Drug therapy of disseminated forms of breast cancer involves the use of monoand polychemotherapy with the possible combination with target-therapy in various clinical situations. The article presents the choices of treatment approaches, demonstrated the efficacy and safety of chemotherapeutic regimens on the basis of vinorelbine